CT and pathological features in renal parenchymal malakoplakia: a case report and review of the literature - Yang, Yuanfen (Aktuelle Urologie, 2021)
Renal malakoplakia is a rare form of chronic inflammatory granulomatous disease in the kidney. It occurs in adult patients with immunocompromised status or debilitating disease. In the present study, we reported a case of a 50-year-old woman with no underlying disease. This report describes the CT and pathological features of renal malakoplakia in a 50-year-old woman. Plain CT scan showed a large soft tissue mass at the middle and upper pole of the left kidney. Enhanced CT scan showed delayed enhancement in the solid part of the mass. Our results might provide some useful information for the diagnosis of renal parenchymal malakoplakia.
Keywords: Malakoplakie; Michaelis-Gutmann-Körper; CT